On-Orbit Results of Photoelectron Current Measurement System in Low Earth Orbit on HORYU-IV Satellite - Ewang, E.; Ogah, O.; Suleiman, H.; Agbaje, G.; Faizullin, D.; Toyoda, K.; Cho, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
On-orbit photoelectron current experiment is one of the missions carried out with the less resource available from a HORYU-IV satellite, for measuring the current from metallic and insulator surfaces from air mass zero (AMO) spectrum. This is with the view to determined photoelectron potential of materials widely used in spacecraft in space. HORYU-IV also known as Arc Event Generator and Investigator satellite (AEGIS) is among HORYU satellite series of Kyushu Institute of Technology, which was launched on February 17, 2016 as a piggy-back on-board H-IIA rocket. The measurement system consists of current-voltage amplifier circuits for Au, Kapton and Black Kapton samples with varying gains and other discrete components. We present the analysis of the telemetry data obtained after the launch; validate the effectiveness of the design and verification processes. The results show that the current measured from Black kapton sample surface had 1.80 nA and 2.70 nA, corresponds to 69.1ᵒ and 75.1ᵒ minimum and maximum elevation angles respectively. This paper described the on-orbit result of PEC and its verification through ground tests.